Effect of environmental and socioeconomic factors of the household on the chronic malnutrition of children under 5 years old in Peru - Paredes Mamani, René Paz (2020)
The objective of the research was to show the effects generated by socioeconomic and environmental factors at the household level on chronic child malnutrition in Peru, for this purpose, the Demographic and Family Health Survey (ENDES) corresponding to the year 2018, and a model of logit regression to find the results. The main research findings suggest the following. Regarding socioeconomic factors, the mother's education and the household wealth index are important predictors for the reduction of chronic child malnutrition, on the side of household environmental factors, chronic child malnutrition is directly related to type of sanitary facilities, the source of drinking water, the floor and wall of the dwelling, type of fuel for cooking, the type of fuel for cooking, sanitary facilities, and the ways of elimination of feces from young children. The more inadequate the environmental conditions of the home, the greater the probability that the child will be chronically malnourished and viceversa.